Maintenance of the DNA puff expanded state is independent of active replication and transcription. - Mok, E.H.; Smith, H.S.; DiBartolomeis, S.M.; Kerrebrock, A.W.; Rothschild, L.J.; Lange, T.S.; Gerbi, S.A. (Chromosoma, 2001)
The maintenance of the expanded state of DNA puffs II/2B and II/9A in polytene chromosomes from stage 14 x 7 Sciara coprophila salivary glands was assayed after inhibition of RNA synthesis, DNA synthesis, or both processes together. Heat shock conditions were established in order to inhibit transcription. Polypeptides of Mr 72,000 and 36,000 were produced in Sciara after heat shock. The gene encoding the Mr 72,000 polypeptide, the homolog of Drosophila hsp70, was cloned. In situ hybridization detected Sciara hsp70 at bands 4A and 17C on chromosome IV. Sciara hsp70 encodes a 2.3 kb heat shock mRNA. DNA puffs (e.g., DNA puffs 2B and 9A on chromosome II) remained fully expanded even after inhibition of transcription by heat shock or actinomycin D, or after inhibition of DNA replication by aphidicolin, or inhibition of both RNA synthesis and DNA synthesis together by actinomycin D plus aphidicolin. Therefore, maintenance of the DNA puff expanded state in Sciara does not require ongoing transcription and/or replication. Mechanisms for initiation and for maintenance of puffs (open chromatin structure) are discussed.